PORNOGRAFI DAN PORNOAKSI DI ANTARA KERAGAMAN NILAINILAI BUDAYA - Musarrofa, Ita (Islamic University of Indonesia, 2006)
Nowadays the member of Indonesian Senate discuss about the proposed academic manuscript regarding pornography and pornoaction. And this act becomes priority over that of other regulation. But, the articles of the act emerge controversies. The controversies because of the plurality of Indonesian cultures. The question is how the differences of cultures influence on society perspective concerning pornography and pornoaction. According to the writer of the following article it needs to be reflecting the relation between morality and law in Indonesia, including the act of pornography and pornoaction. Kata kunci: pornografi, pornoaksi, kontroversi, moral, dan budaya.